Bank of industry’s small and medium enterprise programme: an exploratory impact analysis on the livelihood status of poultry farmers in Nigeria (International Journal of Agricultural Research, Innovation and Technology, 2025)
The study evaluated how the small and medium business (SME) program of the Bank of Industry (BOI) affected the livelihood situation of chicken producers in Osun State, Nigeria. Using a two-stage sampling process, data was gathered using a structured interview schedule from 185 beneficiaries (poultry farmers) who were chosen at random from each of the six administrative zones. Descriptive statistics were utilized to analyze the data, and inferential conclusions were drawn using paired sample t-tests, correlations, and chi-square. The survey found Osun State's small and medium-sized poultry producers now have better living conditions thanks to the BOI's SME programme. It was observed that the programme brought about an increase in innovative thinking and ideas of the beneficiaries. However, there was a significant association between the socio-economic characteristics of the beneficiaries and their livelihood status; it revealed a significant difference (t= 21.424; P ≤ 0.05) in the livelihood status of the respondents before and after the programme, which implies that respondent’s income increases, experience tremendous growth in business output and were able to acquire more assets; hence, the programme should be sustained by successive government’s administration and should be extended to other enterprises.Int. J. Agril. Res. Innov. Tech. 15(1): 88-98, June 2025